(untitled) (Psicologia USP, 2011)
The article aims to discuss issues related to frequent controversy in the Psychology of Learning, which consist on the relationships between cognition, culture affect and human specifics on these processes. Thus, learning is discussed in terms of shared processes with other species such as association and recursion, and others that are specifically human, such as abstraction and metacognition. We examine some hypotheses about how the human mind may have evolved in direction of these differences. At the conclusion, it is specified the position about the links between cognition, affection and culture, as well about levels of human functioning, and the decisive role of culture and its main instrument, language, in favoring the development of human specifics.